Geomorfologi Daerah Tambang Emas Rakyat Juriya dan Sekitarnya, Kecamatan Bilato, Kabupaten Gorontalo - Rauf, Jayanti; Arifin, Yayu Indriati; Akase, Noviar (Journal of Applied Geoscience and Engineering, 2024)
This study examines the geomorphological characteristics of the Juriya people's gold mining area, Gorontalo Regency, which includes topographic variations, slopes, river flow patterns, river stadia, and geomorphological units. The research area is divided into four main morphometry types: Lowland, Inland Lowland, Low Hill, and Hill. Slope analysis identifies zones ranging from flat to very steep, indicating different levels of slope stability and areas with a high risk of erosion. The results of the river flow pattern analysis showed the dominance of parallel and dendritic patterns, with a "V" shaped valley in the young stadia and a "U" in the adult stadia. The geomorphological units in the study area consist of the Volcanic Hills Unit, the Denudional Hills Unit, and the Aluvial Plains Unit, each of which has unique lithological and topographic characteristics and affects land use and environmental stability. This study shows that mining activities can increase the risk of erosion and land degradation in areas that are not protected by vegetation, especially on steep slopes. This research contributes by providing geomorphological data that can be used as a reference for sustainable environmental planning and management in the mining area. These results can strengthen efforts to mitigate environmental risks and support responsible land use in people's mining areas.